Pengaruh Muka Air Tanah dan Pupuk Nitrogen terhadap Emisi Karbon Tanaman Padi di Tanah Gambut - Muh Bambang Prayitno; Putri Elia Ayu Runtung; Yaswan Karimuddin (Seminar Nasional Lahan Suboptimal, 2018)
Prayitno et al, 2019.  The Effect of Ground Water Level and Nitrogen Fertilizers on the Plant Carbon Emission on Peat Soil. pp. 225-235.The aimed of study was to determine the increase of CO2 gas emissions in rice plants on peat soil which is influenced by ground water level and nitrogen fertilizer and to know the type of treatments that affects the highest CO2 gas emissions. The study was conducted at the green house, Faculty of Agriculture, Sriwijaya University, Inderalaya. The results showed that in the 5 cm water level from the soil surface and the application of nitrogen fertilizer of 250 kg/ha had significant effect on CO2 emission. The highest CO2 gas emissions during the growth period is generated by the water treatment of -5 cm from the soil surface and the application of nitrogen fertilizer of 250 kg/ha, about 2619.54 mg. The lowest CO2 emissions during the growth period were generated by the treatment of water level +5 cm from the soil surface and the application of fertilizer of 125 kg/ha, were about 348.30 mg. Total CO2 emissions during one growth period is 39699.15 mg. The results of this study can be as a recommendation for rice planting activities.